A REVIEW ON THE USE OF PLANT SEEDS IN WATER TREATMENT - P. R. O., Edogbanya1*; J. O., Obaje (university of eloued جامعة الوادي, 2020)
Global population, which has been estimated by United Nations to hit 9.8 Billion by the middle of this century and the corresponding demand for clean, affordable and portable water, which is not readily available, especially for developing countries and even developed ones, has become a course for concern. It is estimated that 1.2 billion people lack access to clean drinking water and about 2.2 million people die annually, mostly of children under five due to consumption of unsafe water. The use of inorganic chemicals in treating water is fast becoming problematic, as it is associated with different deteriorating human health condition and pollution of water bodies. Simple to complex methods are involved in this, but the general procedure involves, collection of plant seeds, drying, grinding/extraction of active compounds and its application in water sample.
artical
Keywords: Biocoagulation; Biodisinfection; Bioresource; Biosorption; Plant Seeds. Water Treatment